Preparation and Validation of Fe2O3 Modified Carbon Paste Electrode for Measurement of Dopamine by Voltammetry Method - Irdhawati Irdhawati; Manuntun Manurung; Ni Ketut Yuni Sri Lestari (Jurnal Kimia Sains dan Aplikasi, 2019)
Preparation and validation of the Fe2O3 modified carbon paste electrode have been carried out for the analysis of dopamine by the voltammetry method. Validation parameters of carbon paste electrodes (CPA) tested include linear concentration range, Limit of Detection (LoD), Limit of Quantification (LoQ), accuracy, and selectivity in the presence of ascorbic acid and uric acid. The results obtained in the optimization of the composition and condition of the Fe2O3 modifier in graphite are 0.8% mass at pH 6 solution with the Brinton Robinson buffer solution. The peak potential shifted 32 mV in the negative direction from the initial peak potential of 319 mV at the carbon paste electrode without modification to the peak potential of 287 mV at the 0.8% Fe2O3 modified carbon paste electrode. The linear concentration range at concentrations of 8 µM–100 µM obtained a linear equation y= 1.1204 + 0.1289x with R2=0.99943. LoD value obtained is 0.23 µM, and the LoQ is 0.77 µM. In the selectivity test obtained in the dopamine analysis using 0.8% Fe2O3 modified carbon paste electrode, the anodic peaks of dopamine (75 mV), ascorbic acid (190 mV), and uric acid (200 mV) can be separated. This method has acceptable repeatability because it produces a Horwitz Ratio value of 0.0417, which is smaller than two. Preparation and validation of 0.8% Fe2O3 modified carbon paste electrode can be declared as eligible for the measurement of dopamine.